PTU-201 Living with anal fistulae. (22nd June 2015) - Yassin, NA; Dibley, L; Nachiappan, S; Phillips, R; Hart, A; Norton, C
Abstract : Introduction: Around one in 10, 000 people develop an idiopathic anal fistula and one third of patients with Crohn's disease (CD) develop perianal fistulae. The associated morbidity of anal fistulae and its treatments can have profound effects on patients. The inflammatory bowel disease questionnaire (IBD-Q) has been used to assess the quality of life (QoL) of Crohn's fistula patients on anti-TNF therapy. The Perianal Disease Activity Index (PDAI) has been used for the assessment of Crohn's anal fistulae, although it mostly covers clinical aspects of the disease. Neither the IBD-Q nor the PDAI explore issues relating specifically to perianal fistulae. There are no specific idiopathic anal fistula QoL assessment tools. The aim of this study was to gain an understanding of the experience of perianal fistulae for Crohn's and idiopathic fistula patients. Method: Crohn's and idiopathic fistula patients were identified from outpatient clinics, and invited to participate after reading the patient information sheets. Semi-structured interviews were conducted on 25 consenting fistula patients (20 Crohn's, 5 idiopathic). Interviews were transcribed verbatim, and transcripts analysed independently by two researchers using a thematic analysis approach as guided by Colaizzi's framework. Themes were identified relating to the experience of living with anal fistulae. Results: Nine central themes were identified: diagnosis and acceptance (relief at getting a diagnosis which was explained to them), decision making (patients involvement in their treatment plan), coping strategies (having people around to provide support, or stocks of medical supplies in case of flares), body image (affecting patients' self-esteem), stigma (including self- and perceived-stigma), relationships (detailing the difference between intimacy and companionship), social implications (including daily living activities and holidays), education and work (and the requirements for life adjustments) and clinical care issues such as having information regarding medical and surgical issues. Each of these main themes was divided into several subthemes. Conclusion: Crohn's and idiopathic anal fistulae are a major cause of distress and greatly impact on patients' lives. The study findings have revealed new insights into specific issues related to living with perianal fistulae. These issues may lead to emotional, social, work-related and financial restrictions, which should be appreciated by health care professionals. There is a need for further research in this area to improve our understanding of the impact of anal fistulae on patients' QoL and develop appropriate assessment tools designed specifically for this group of patients. Disclosure of interest: None Declared.